2011
DOI: 10.1152/jn.00995.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of cognitive control of reaching movements in the dorsal premotor cortex of rhesus monkeys

Abstract: Canceling a pending movement is a hallmark of voluntary behavioral control because it allows us to quickly adapt to unattended changes either in the external environment or in our thoughts. The countermanding paradigm allows the study of inhibitory processes of motor acts by requiring the subject to withhold planned movements in response to an infrequent stop-signal. At present the neural processes underlying the inhibitory control of arm movements are mostly unknown. We recorded the activity of single units i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
166
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 79 publications
(122 reference statements)
20
166
1
Order By: Relevance
“…In a later section we will argue that the same system comes into play when a motor plan must be suppressed. In fact, the measured neural latency in response to the target jump is comparable to what has been reported in the same part of PMd using the Stop task (Mirabella et al, 2011).…”
Section: Timing Of Cell Activity During Correction Signalingsupporting
confidence: 85%
See 1 more Smart Citation
“…In a later section we will argue that the same system comes into play when a motor plan must be suppressed. In fact, the measured neural latency in response to the target jump is comparable to what has been reported in the same part of PMd using the Stop task (Mirabella et al, 2011).…”
Section: Timing Of Cell Activity During Correction Signalingsupporting
confidence: 85%
“…Recent evidence (Kaufman et al, 2013;Merchant et al, 2008) shows that putative inhibitory interneurons in M1, classified using the trough-to-peak duration of the unfiltered extracellular spike waveform, increase their discharge at the time of movement generation (however, see Vigneswaran et al, 2011 for a specific comments on this method when applied to M1). Different sub-populations of neurons showing preparatory activity during successful inhibition of reaching movements in PMd display either a reduction or an increase in their activity (Mirabella et al, 2011); this is compatible with both of the functional pathways referred to above.…”
Section: Neurophysiological Studies In Animalssupporting
confidence: 76%
“…A related study demonstrated modulation of local field potential in the SMA/pre-SMA prior to cancelation, but the modulation occurs for different frequency bands, which raises question as to its general role in response inhibition . These no-go or countermanding activities have also been reported for the PMd (Mirabella et al, 2011). Specifically, in an SST, approximately one-third of PMd neurons show movement preparatory activities modulated during stop success trials prior to the end of the estimated SSRT.…”
Section: Inhibition Of Manual Movementsupporting
confidence: 59%
“…In the SMA, a mesial PM area influencing the spinal cord and other cortical motor centres in the frontal lobe but unable to participate directly in the control of motor generation [40], single unit activity, multiunit activity or local field potentials (LFPs)-activities, with slight differences, are related to the level of proactive control [27]. Surprisingly, in the PMd, where neurons predict whether an action will be executed in stop trials (these neurons have similar characteristics as FEF neurons; see Discussion in [41]), a different relationship of history-dependent behavioural performance and neural modulation was reported by Marcos et al [28]. These authors showed that the PMd informs response adjustments following different types of trials only by across-trial firing variability, measured as variance of the conditional expectation [42], and not by changes in the average single unit firing rate (figure 2c,d).…”
Section: Recent Actions Impact Future Behaviour and Neural Activitymentioning
confidence: 99%